A study on the effect of add-on rosiglitazone on the ankle-brachial pressure index of patients with type 2 diabeties mellitus in Hospital Universiti Sains Malaysia - Mustaffa, Nazri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Background Rosiglitazone, an oral hypoglycaemic agent of the thiazolidinedione group is used for Type 2 Diabetes treatment. Research has shown that this medication, being a peroxisome proliferator activator receptor-gamma agonist has effects beyond glycaemic control alone. Apart from improving insulin resistance, the nonhypoglycaemic effects of rosiglitazone include reduction of inflammatory markers, improvement of endothelial function, improvement in fibrinolytic activity as well as changes in cholesterol profile. This study aims to assess changes in surrogate markers of atherosclerotic burden via ankle-brachia! pressure index measurements, the number of patients who have significant peripheral artery disease in the study, changes in the diabetic prothrombotic state via serum plasminogen activity, changes in glycaemic control via HbA1c and changes in cholesterol profile by measuring total-, high density lipoprotein- and low density lipoprotein-cholesterol after rosiglitazone is added to a -- .. :,· '.-,··-, pre-existing Type 2 Diabetes treatment regime. Methods A non-blinded cross-sectional cohort study was designed. 59 patients were enrolled. Patients who were rosiglitazone naYve were prescribed 4mg of oral rosiglitazone for a period of 10 weeks. The main objectives were to assess the changes in ankle-brachia! pressure index readings as well as changes in serum fibrinolytic markers pre- and post-treatment of add-on rosiglitazone. Secondary objectives were to assess the number of patients in the study who had significant peripheral artery disease, to assess the changes in glycaemic control and to measure changes in cholesterol profile at the end of the study period. Results 48 patients completed the study. Mean ankle-brachia! pressure index was 1.06 ± 0.12 pre-, and 1.07 ± 0.13 post-rosiglitazone. Difference in means was - 0.012. p-value was 0.439. 4 patients (8.3%) had an ABPI ratio of less than 0.90 indicating presence of significant peripheral artery disease. Mean serum plasminogen activity(%) was 96.00 ± 14.77 before rosiglitazone, and 111.98 ± 15.83 after. Means difference was -15.977, with a p-value of 0.006. Initial mean HbA1c (%)was 9.76 ± 2.06, and second mean was 9.25 ± 2.03, with a difference of 0.510. p-value was <0.001. Mean total cholesterol (mmol/L) was 4.95 ± 1.02 before rosiglitazone and 5.32 ± 0.94 after. Change in means was -0.364 with p=0.003. Mean high density lipoprotein cholesterol (mmol/L) at the beginning was 1.32 ± 0.37 and 1.47 ± 0.41 at the end, with a -0.150 difference. P<0.001. Finally, mean low density lipoprotein cholesterol (mmol/L) concentration was 2.89 ± 0.85 at the start and 3.08 ± 0.96 at the end. Difference in means was -0.193, with a p-value of 0.098. Conclusion This ., Sfuey slibws that oral xrosrglitaiorie "4mg datTy-Sigrii:ficantly improves serum plasminogen activity levels, probably indicating improvement in fibrinolytic activity. There is also a significant reduction in HbA10 , rise in total cholesterol as well as high density lipoprotein-cholesterol levels in line with the findings of previous studies. The rise in ankle-brachia! pressure index and low density lipoprotein-cholesterol measurements however, were not significant in this study. Not many patients had significant peripheral artery disease in this study compared to previous ones before this. Overall, this study shows that rosiglitazone indeed has effects beyond hypoglycaemic action with regards to improvement in the diabetic prothrombotic state as well as cholesterol profile. However, more research is needed regarding the relation between use of rosiglitazone and atheroma reduction.